Optimasi Pupuk NPK Majemuk, Pupuk Daun Dan POC Urin Sapi Pada Hidroponik Sistem Wick Terhadap Produksi Tanaman Kubis Bunga (Brasicca oleracea L. Var. Botrytis Sub.Var. Cauliflora DC) Kultivar PM 126 F1 - Rommy Andhika Laksono; Sugiono D. (Paspalum: Jurnal Ilmiah Pertanian, 2019)
There are several factors that cause a decrease in the production of Cabbage Flowers in Indonesia, including inadequate cultivation systems, less optimal nutrition, and a lack of utilization of organic elements in cultivation techniques, as well as the use of urban narrow land. The purpose of this study was to study and obtain a combination of compound NPK fertilizer, leaf fertilizer and POC cow urine which gave the highest production of PM 126 F1 variety flower cabbage plants on the wick hydroponic system. This research was conducted at Screen House, located in West Jomin Village, Kota Baru Subdistrict, Karawang Regency, West Java Province. The research site is at an altitude of 10 meters above sea level, from April to September 2018. The method used is the experimental method and the experimental design used was Randomized Block Design (RBD) consisting of 10 treatments repeated 3 times. Data were analyzed using variance analysis and further testing with Duncans multiple range test at the level of 5%. The results of this study are compound NPK fertilizer optimization, leaf fertilizer and POC cow urine on the wick hydroponic system that have a significant effect on growth components (plant height 42 days, number of leaves 42 days, stem diameter 42 days, root display, and leaf area), and gave a significantly different effect on the yield component (flower height, flower diameter, leaf weight without leaves, and flower weight with leaves) flower cabbage plant cultivar PM126F1. Treatment A (AB Mix 10 ml L-1 water) gave the highest yield on flower weight (crop) with leaves per plant of 536.056 gr equivalent to 22.34 tons per hectare and weight of flowers (crop) without leaves per plant of 207.57 gr equivalent to 8.65 tons per hectare.